(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2017)
After reviewing the historical and cultural references of Italian linguistic Purism, this article examines the role that the phraseological ways have in writing, according to its founder Antonio Cesari. In his opinion phraseology symbolizes the couple “nature” and “people” an exemplary exemplary way, justifying the restoration of the fourteenth century Florentine language. In particular, this article focuses on a sample of text extrapolated from the translation made by Cesari of a comedy of Terence. It shows that the translator does not use paraphrases to translate in the Italian language idiomatic expressions present in the Latin text, but he uses phraseological forms characterized by communicative equivalence that reproduces the “natural” and “popular” meaning of the Latin text.